Disturbance of circadian rhythms in analgosedated intensive care unit patients with and without craniocerebral injury - Paul, Torsten; Lemmer, Björn (Chronobiology international, 2007)
Melatonin, cortisol, heart rate, blood pressure, spontaneous motor activity, and body temperature follow stable circadian rhythms in healthy individuals. These circadian rhythms may be influenced or impaired by the loss of external zeitgebers during analgosedation, critical illness, continuous therapeutic intervention in the intensive care unit (ICU), and cerebral injury. This prospective, observational, clinical study examined 24 critically ill analgo‐sedated patients, 13 patients following surgery, trauma, or acute respiratory distress (ICU), and 11 patients with acute severe brain injury following trauma or cerebral hemorrhage (CCI). Blood samples for the determination of melatonin and cortisol were obtained from each patient at 2 h intervals for 24 h beginning at 18:00 h on day 1 and ending 16:00 h on day 2. Blood pressure, heart rate, body temperature, and spontaneous motor activity were monitored continuously. Level of sedation was assessed using the Ramsey Sedation Scale. The severity of illness was assessed using the APACHE‐II‐score. The time series data were analyzed by rhythm analysis with the Chronos‐Fit program, using partial Fourier series with up to six harmonics. The 24 h profiles of all parameters from both groups of patients were greatly disturbed/abolished compared to the well‐known rhythmic 24 h patterns in healthy controls. These rhythm disturbances were more pronounced in patients with brain injury. The results of this study provide evidence for a pronounced disturbance of the physiological temporal organization in ICU patients. The relative contribution of analgosedation and/or brain injury, however, is a point of future investigation.